Poznański Czerwiec i rok 1956 – historia i pamięć po sześćdziesięciu latach - Sasanka, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article is a brief survey and evaluation of historical research on Poznań 1956 protests, the political change in October 1956, and the year in general. An important gap was filled by the publication of Piotr Grzelczak’s book on the long-term consequences of the Poznań protests, and the conflict over its remembrance between government representatives and local inhabitants of the region, since the protests were one of the defining moments in recent history of Poznań. The article also includes a summary of the controversy between historians over the importance of 1956 as a watershed in Polish history, with some historians arguing that a more liberal image of the communist system in Poland was formed in 1956, while others argued that the communist dictatorship was stabilized by winning wider social support. The author has indicated an increasing separation between narratives about the Poznań protests in June and the political transformations in October, which has consequences and threats related to polarized perception of history, leading to meagre and simplified understanding of social realities of the Polish People’s Republic after 1956.